Acute post-traumatic stress symptoms and age predict outcome in military blast concussion - Mac Donald, Christine L. (Brain, 2015)
High rates of adverse outcomes have been reported following blast-related concussive traumatic brain injury in US military personnel, but the extent to which such adverse outcomes can be predicted acutely after injury is unknown. We performed a prospective, observational study of US military personnel with blast-related concussive traumatic brain injury (n = 38) and controls (n = 34) enrolled between March and September 2012. Importantly all subjects returned to duty and did not require evacuation. Subjects were evaluated acutely 0–7 days after injury at two sites in Afghanistan and again 6–12 months later in the United States. Acute assessments revealed heightened post-concussive, post-traumatic stress, and depressive symptoms along with worse cognitive performance in subjects with traumatic brain injury. At 6–12 months follow-up, 63% of subjects with traumatic brain injury and 20% of controls had moderate overall disability. Subjects with traumatic brain injury showed more severe neurobehavioural, post-traumatic stress and depression symptoms along with more frequent cognitive performance deficits and more substantial headache impairment than control subjects. Logistic regression modelling using only acute measures identified that a diagnosis of traumatic brain injury, older age, and more severe post-traumatic stress symptoms provided a good prediction of later adverse global outcomes (area under the receiver-operating characteristic curve = 0.84). Thus, US military personnel with concussive blast-related traumatic brain injury in Afghanistan who returned to duty still fared quite poorly on many clinical outcome measures 6–12 months after injury. Poor global outcome seems to be largely driven by psychological health measures, age, and traumatic brain injury status. The effects of early interventions and longer term implications of these findings are unknown.